A 0.8 – 2.4 Gbps Driver With Adjustable De-Emphasis Scheme For Ddr3 Memory Interface - Lim, Zong Zheng (2014)
The need for greater memory bandwidth to boost the computer system performance has driven system memory evolution to Double Data Rate Synchronous Dynamic Read Access Memory (DDR SDRAM) technologies. Trends to maximize memory bandwidth have caused Inter-Symbol Interference (ISI) become significant which degraded the signal integrity of transmitted data. In this research, a driver architecture with adjustable de-emphasis and impedance control scheme is proposed for high-data rate and high-density DDR3 SDRAM memory system. The proposed driver is implemented using 45 nm CMOS process technology. The designs and implementations of the proposed driver involve the design of driver architecture, data controller, impedance calibration block with reference generator as well as the layout for critical analog circuits i.e. three driver segments for post-layout simulations to ensure the parasitic in layout does not has significant effect on driver performances. The driver has 15 de-emphasis legs that can form 15 de-emphasis voltage levels that capable of reducing ISI-induced jitter at high operating frequency. Moreover, high density DDR3 memory system can deteriorate the far-end eye jitter and eye height that causes difficulties in data sampling and recovery. Thus, the driving impedance of the proposed driver can be programmed between 20, 30 and 40 Ω to compensate the variability of board routing effect in memory system and hence, improving signal integrity.